School librarians’ readiness for information literacy implementation in secondary schools / Tan Shyh Mee - Tan, Shyh Mee (2014)

(untitled)
The literature suggests that information literacy education is embedded and integrated in the Malaysian Integrated Primary (1982), the Secondary School Curriculum and the Curriculum Standard for Primary School (2012-2015). However, there is no concrete empirical research to confirm or deny the implementation of information literacy in the school curriculum. This study focuses on the implementation of information literacy education (ILE) in Malaysian secondary schools and the role of the school librarian. The main aims of the study were to determine the readiness of the school librarians towards the implementation of information literacy in schools and identify factors that influence information literacy implementation in Malaysian school librarians. This is a quantitative research, using descriptive research design and survey research technique with two distinct data collection techniques; a semi structured interview and a survey involving 710 school librarians in Malaysia. School librarian readiness is defined as their preparedness to implement IL and it is derived as the cognitive, functional and technical readiness of school librarians in IL implementation. Findings reveal that school librarians’ professional qualifications have an impact on their cognitive, functional and technical readiness. However, their experience as a school librarian has a significant impact on technical readiness only. The study established four organizational factors influencing the implementation of ILE, mainly Professional Development, Teaching and Learning Strategies, Information Literacy Policies & Standards and Infrastructure. The researcher proposes an IL Implementation framework that emphasizes two main contributors to the successful implementation of ILE in Malaysian schools: School Librarians’ Readiness and the Organizational Factors.